Observer variability in histopathological reporting of malignant bronchial biopsy specimens. Issue 8 (August 1994) - Burnett, R A; Swanson Beck, J; Howatson, S R; Lee, F D; Lessells, A M; McLaren, K M; Ogston, S; Robertson, A J; Simpson, J G; Smith, G D
Abstract : AIMS--To evaluate the ability of histopathologists to classify lung carcinomas on bronchial biopsy material using the current World Health Organisation (WHO) classification. METHODS--Eleven histopathologists each reviewed 100 randomly selected bronchial biopsy specimens which had originally been reported as showing lung carcinoma. A single haematoxylin and eosin stained section from each case was circulated and a standard proforma completed. These were analysed using kappa statistics. RESULTS--The histopathologists were excellent at distinguishing between small cell and non-small-cell carcinoma kappa = 0.86), but not so good at subclassifying the non-small cell carcinoma group kappa = 0.25). CONCLUSIONS--The clinically important distinction between small cell and non-small cell carcinoma of the lung is reliably made by competent histopathologists even on limited material.